Superior conductive polypyrrole anti‐corrosion coating doped with titanium nitride for 304 stainless steel bipolar plates. Issue 12 (18th January 2023) - Ding, Guoxin; Wang, Chen; Gao, Nan; Li, Ruofan; Wang, Yunpeng; Ma, Haitao
Abstract: The conductivity and corrosion performance of metallic bipolar plates were crucial to the development of the proton exchange membrane fuel cell (PEMFC). In this study, polypyrrole (PPy) coatings doped with titanium nitride nanoparticles (TiN NPs) were deposited on 304 stainless steel (304SS) by constant potential polymerization. To improve dispersion and form a negative charge surface, TiN NPs were modified by anionic surfactants such as sodium dodecyl diphenyl ether disulfate (MADS). Through comparing potentiodynamic curves of the composite coatings in the simulated cathodic environment of PEMFC, the PPy‐0.1 TiN (0.1 g/L) coating presented a more positive corrosion potential ( E corr  = 293 mVAg/AgCl ) and a lower corrosion current ( I corr  = 0.841 μA cm −2 ). Furthermore, PPy‐0.1 TiN exhibited more stable corrosion resistance during long‐term immersion. Interfacial contact resistance (ICR) testing demonstrated that the addition of TiN NPs improved conductivity compared to a PPy coating. The results indicated that the PPy‐TiN‐coated 304SS could be used as a kind of promising bipolar plate material. Abstract : Superior conductive polypyrrole/ titanium nitride composite coatings with anti‐corrosion and hydrophobicity properties.